Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd000198
|View full text |Cite
|
Sign up to set email alerts
|

Support during pregnancy for women at increased risk of low birthweight babies

Abstract: Updated literature search resulted in addition of two included trials (Brooten 2001;Dawson 1999) and two excluded studies (Ford 2002; Graham 2003). The additions led to minor modifications in test statistics but did not lead to changes in the conclusions of the Review.Two trials await assessment (Beazley 2001;Nguyen 2003), one because only a brief abstract was available and the other because the reported results are for a portion of the final sample.Typos were corrected. One study ID was changed to reflect th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 59 publications
2
78
0
Order By: Relevance
“…The researchers suggested that this kind of support by relatives should be studied in countries where it is not currently available. Support during pregnancy provided to pregnant women at risk of having low birth weight babies may be helpful in reducing the likelihood of cesarean delivery, although it is unlikely to reduce the occurrence of preterm deliveries and low birth weight infants [9]. Continuous support of women provided during labor by any type of "supporter," including nurses, midwives, or lay people, has been reported as beneficial for shorter duration of labor, a spontaneous vaginal delivery, less requirement for intrapartum analgesia, and a more positive birth experience [10].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggested that this kind of support by relatives should be studied in countries where it is not currently available. Support during pregnancy provided to pregnant women at risk of having low birth weight babies may be helpful in reducing the likelihood of cesarean delivery, although it is unlikely to reduce the occurrence of preterm deliveries and low birth weight infants [9]. Continuous support of women provided during labor by any type of "supporter," including nurses, midwives, or lay people, has been reported as beneficial for shorter duration of labor, a spontaneous vaginal delivery, less requirement for intrapartum analgesia, and a more positive birth experience [10].…”
Section: Discussionmentioning
confidence: 99%
“…Practical support such as housekeeping and childcare assistance, educational support, emotional support, social support have variously been associated with levels of satisfaction and women's physical and emotional health. [31][32][33] However, understanding which women benefit most from which type of support and when that support is required is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nolan (1997) suggested that these sessions should include information relating to parenthood. A Cochrane review endorsed antenatal education as an important role in improving maternal perinatal psychological outcomes (Hodnett, 2000). The 'brick wall approach' theory suggested by Wiener (2002) postulates that while pregnant, women are unable to receive information regarding parenthood.…”
Section: Education and Preparation For Parenthoodmentioning
confidence: 99%